Pengaruh Karakteristik Individu, Sikap dan Persepsi terhadap Perilaku Kewirausahaan (Studi pada Industri Kecil Kerajinan Tangan dan Handycraft di Kabupaten Lamongan) - Badriyah, Nurul (Universitas Brawijaya, Indonesia, 2011)
The small industry plays important role in the national economic. This industry is made of large, medium and small entrepreneurship activities. It has been managed by any individuals through their idea, personal objective, and ambition to produce good combination of resource. They have different skill from others in the character, attitude and perception on business. The objective of research is (1) to analyze the effect of individual characteristic, attitude and perception simultaneously on entrepreneurship behavior, (2) to analyze the effect of individual characteristic, attitude and entrepreneurship partially on entrepreneurship behavior, and (3) to analyze the dominant variable affecting entrepreneurship behavior. This research is conducted on the entrepreneurs of handicraft industry at Lamongan Regency. Result of research indicates that individual characteristic, attitude and perception positively and simultaneously affect entrepreneurship behavior. In partial manner, the dependent variable positively and significantly influences entrepreneurship behavior. Perception is the dominant variable affecting entrepreneurship behavior.